2018
DOI: 10.4995/wrs.2018.7021
|View full text |Cite
|
Sign up to set email alerts
|

Humoral immune response to different routes of myxomatosis vaccine application

Abstract: The aim of our study was to monitor the dynamics of the serological response to different application routes of live attenuated myxomatosis vaccine. The study included 42 Californian breed rabbits, aged 3 mo, of both sexes. They were separated into 7 groups: 6 experimental and 1 control. All experimental groups were vaccinated on day 0 with a single dose of myxomatosis vaccine (min 10<sup>3.3</sup> tissue culture infective dose 50 [TCID<sub>50</sub>], max 10<sup>5.8</sup> TC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…This can also mean that the subcutaneous route is not the ideal primary site of Myxoma virus multiplication or antigen presentation. Several studies have shown the lower effectiveness of the subcutaneous route in inducing immunity compared with the intradermal route [ 27 , 28 ]. The intradermal route allows a longer contact between the antigen and the antigen-presenting cells with a high number of dendritic cells in the derma compared with the subcutaneous tissue [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This can also mean that the subcutaneous route is not the ideal primary site of Myxoma virus multiplication or antigen presentation. Several studies have shown the lower effectiveness of the subcutaneous route in inducing immunity compared with the intradermal route [ 27 , 28 ]. The intradermal route allows a longer contact between the antigen and the antigen-presenting cells with a high number of dendritic cells in the derma compared with the subcutaneous tissue [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…When Myxoma virus is inoculated intradermically, it can enter directly by lymphatic vessels for transport to antigen-presenting cells in the lymph nodes [ 30 ]. Considering the specificity of MYXV to epithelial cells, the delivery to the epidermis or dermis may result in superior and quick immune responses when compared to muscle and subcutaneous tissues [ 28 ]. This explanation can be also applied to the inoculation of virus during the challenge.…”
Section: Discussionmentioning
confidence: 99%
“…Some clarity was introduced by the studies of Manev et al (2018), in which different groups of rabbits selected according to the principle of similar pairs were simultaneously vaccinated with a monovalent myxomatous vaccine and an associated vaccine against myxomatosis and hemorrhagic disease. When using a monovalent vaccine, antibody titers significantly exceeded the corresponding number of immunocompetent cells against myxomatosis after immunization with the associated vaccine (Bogoyavlenskiy et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Protection with homologous vaccines offers longer lasting immunity than with the heterologous vaccines. Myxoma virus causes immunosuppression in rabbits [18] and one of the main drawbacks to the use of homologous vaccines may be associated with such immunosuppression [18,19] that could exacerbate underlying subclinical infections.…”
Section: Control and Preventionmentioning
confidence: 99%
“…Serological tests exist for the detection of anti-myxoma virus antibodies [19,66,67]. This analysis is of particular importance in farmed rabbits where vaccination is used.…”
Section: Diagnosismentioning
confidence: 99%